Cost-effectiveness of a potential group B streptococcal vaccine for pregnant women in the United States. Issue 45 (27th October 2017) - Kim, Sun-Young; Nguyen, Chi; Russell, Louise B.; Tomczyk, Sara; Abdul-Hakeem, Fatimah; Schrag, Stephanie J.; Verani, Jennifer R.; Sinha, Anushua
Highlights: IAP for pregnant women colonized with group B streptococcus (GBS) has reduced neonatal GBS disease. GBS nonetheless remains a leading cause of neonatal sepsis, with 1000 late-onset cases annually. Maternal GBS vaccine could be an attractive alternative to IAP if the vaccine is about 90% effective. Maternal vaccine as an adjunct to IAP is an expensive strategy, costing $115, 400-$358, 900 per QALY. Coverage, typically low for maternal vaccines, is key to the vaccine's impact on GBS disease. Abstract: Background: In the U.S., intrapartum antibiotic prophylaxis (IAP) for pregnant women colonized with group B streptococcus (GBS) has reduced GBS disease in the first week of life (early-onset/EOGBS). Nonetheless, GBS remains a leading cause of neonatal sepsis, including 1000 late-onset (LOGBS) cases annually. A maternal vaccine under development could prevent EOGBS and LOGBS. Methods: Using a decision-analytic model, we compared the public health impact, costs, and cost-effectiveness of five strategies to prevent GBS disease in infants: (1) no prevention; (2) currently recommended screening/IAP; (3) maternal GBS immunization; (4) maternal immunization with IAP when indicated for unimmunized women; (5) maternal immunization plus screening/IAP for all women. We modeled a pentavalent vaccine covering serotypes 1a, 1b, II, III, and V, which cause almost all GBS disease. Results: In the base case, screening/IAP alone prevents 46% of EOGBS compared to no prevention, at a cost of $70, 275 per quality-adjusted life-year (QALY) from a healthcare and $51, 249/QALY from a societal perspective (2013 US$). At coverage rates typical of maternal vaccines in the U.S., a pentavalent vaccine alone would not prevent as much disease as screening/IAP until its efficacy approached 90%, but would cost less per QALY. At vaccine efficacy of ≥70%, maternal immunization together with IAP for unimmunized women would prevent more disease than screening/IAP, at a similar cost/QALY. Conclusions: GBS maternal immunization, with IAP as indicated for unvaccinated women, could be an attractive alternative to screening/IAP if a pentavalent vaccine is sufficiently effective. Coverage, typically low for maternal vaccines, is key to the vaccine's public health impact.